Success Factors Driving E-Mba Acceptance - MAHMOD, RAZMAH (2004)
E-learning describes the use of information communications technology (ICT) for learning beyond the boundaries of the conventional classroom. Thus, the objective of this study is to determine what are the factors that are significant in explaining intention towards e-learning, particularly e-MBA adoption in Malaysia.